Study on Planning for 150 Kv Outdoor System Substation at Substation Paya Geli, North Sumatra - Jury Yanto Tarigan; Siti Anisah; Hamdani Hamdani (Budapest International Research and Critics University, 2022)
The substation is an important part of the power system. In addition to substations for power generation, they must be able to distribute power reliably and safely. In this study, based on the SPLN standard, I analyzed and calculated the components of the Paya Geli substation so that the selected components could actually conduct electricity properly and safely. The selection of the substation components in Paya Geli was based on these calculations and criteria. From this it can be concluded that the design results of the Paya Geli substation are in accordance with the design.